Development of Content Video Tiktok as a Learning Media to Teach Speaking Skill for Students in SMK Islam 1 Blitar: English - Aisa Diana Amalia; Siti Rofi'ah; Istina Atul Makrifah (Journal of English Development, 2024)
The aim of this study is to develop content video on tiktok applications as a valid or effective technology-based learning media to train the ability to speak English on the procedure text material. The education sector in today's technological age has a strong influence on human resource standards, so for an effective learning process, learning media are needed. Several the methods Borg and Gall by Pantrisia Research and Development(R&D) models were utilized in this study to collect unstructured interviews and observation. There are steps including need analysis, observation and collecting data, product design, validation product, revision product, product testing and revision the product. Researchers selected the subject of this study students of the XI grade major communication engineering and networking 3 in SMK Islam 1 Blitar. Data collection techniques applied were observations, interviews and quesioners. On data analysis researchers use a combination of qualitative and quantitative. The instruments used are observation sheets, validations sheets and quisionare student responses. The three experts also provided the researchers with one valid finding and two very valid results. Validation scores for instruments are 90%, materials are 95%, and media is 75%. These scores indicate that the instruments are appropriate for use as instructional media in procedure text content. Based on the satisfaction questionnaire results about this product, students can use the learning media, and 85% get good answers. Finally, this product can be used as a learning media to train speaking skills in subject.